2013
DOI: 10.3390/w5030988
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future Nutrient Quality of a Small Southeastern River: A Pre-Dam Assessment

Abstract: Riverine dams alter both the physical environment and water chemistry, thus affecting species assemblages within these environments. In the United States, dam construction is on the decline and there is a growing trend for dam removal. The Choctawhatchee, Pea, and Yellow Rivers Watershed Management Authority had initiated the permitting process for placing a reservoir dam on the Little Choctawhatchee River (LCR), a tributary to the Choctawhatchee River. The purpose of the proposed reservoir was water supply, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Water samples were adjusted to pH 7.0 in lab after they were acidified in sampling process, and the concentrations of ammonia (NH 3 -N), nitrate (NO 3 -N), chemical oxygen demand (COD), and total nitrogen (TN) and total phosphorus (TP) were analyzed with HACH DR 2800 spectrophotometer (HACH, Loveland, CO, USA) [25]. Average results of three replicates were used for further analyses.…”
Section: Sampling and Analysesmentioning
confidence: 99%
“…Water samples were adjusted to pH 7.0 in lab after they were acidified in sampling process, and the concentrations of ammonia (NH 3 -N), nitrate (NO 3 -N), chemical oxygen demand (COD), and total nitrogen (TN) and total phosphorus (TP) were analyzed with HACH DR 2800 spectrophotometer (HACH, Loveland, CO, USA) [25]. Average results of three replicates were used for further analyses.…”
Section: Sampling and Analysesmentioning
confidence: 99%
“…Correspondence Analyses confirmed a correlation between higher diatom densities and the increased photic zone following macrophyte removal. most cases above suggested criteria, and (Miller, J. M et al 2013) indicated that water quality of the river was and continues to be nutrient rich. A future reservoir at recent levels of water quality will likely be highly eutrophic, and anthropogenic influences will further stress this ecosystem and its water quality as the urban region expands.…”
Section: Canonicalmentioning
confidence: 99%